Experimental Therapeutics for Challenging Clinical Care of a Patient with an Extremely Rare Homozygous APOC2 Mutation - Masako Ueda; Anna Wolska; Frances M. Burke; Maria Escobar; Laura Walters; Dusanka Lalic; Robert A. Hegele; Alan T. Remaley; Daniel J. Rader; Richard L. Dunbar (Case Reports in Endocrinology)
Background. Among many causes of hypertriglyceridemia (HTG), familial chylomicronemia syndrome (FCS) is a rare monogenic disorder that manifests as severe HTG and acute pancreatitis. Among the known causal genes for FCS, mutations in APOC2 only account for <2% of cases. Medical nutrition therapy is critical for FCS because usual triglyceride- (TG-) lowering medications are ineffective. Therapeutic plasma exchange (TPE) with fresh frozen plasma (FFP) is an option to urgently reduce TG and pancreatitis episodes. Several novel biologics are under development to treat HTG and may provide therapeutic options for FCS in the future. Objective. We present the challenging care of a 43-year-old man with FCS with apoC-II deficiency and the results of two types of TPE and of investigational TG-lowering biologic therapies. Results. The patient’s lipid profile was consistent with FCS. A novel homozygous variant was identified in APOC2, and its pathogenicity was confirmed. Even on a fat-restricted diet, his care was tremendously complicated with unremitting bouts of pancreatitis. TPE with FFP replacement lowered TG >90% post-sessions and appeared to reduce pancreatitis episodes. Experimental ANGPTL3 and APOC3 inhibitors each lowered TG by >50%. Conclusions. Our case demonstrates the importance of delineating and defining the underlying etiology of a rare disorder to optimize therapy and to minimize unfavorable outcomes.